Overexpression of the Prunus sogdiana NBS-LRR Subgroup Gene PsoRPM2 Promotes Resistance to the Root-Knot Nematode Meloidogyne incognita in Tobacco - Zhu, Xiang; Xiao, Kun; Cui, Haiyang; Hu, Jianfang (Frontiers in Microbiology, 2017)
Root-knot nematodes (RKNs), particularly Meloidogyne incognita, are the most devastating soil-borne pathogens that significantly affect the production of Prunus spp. fruit. RKN infection is difficult to control and consequently causes massive yield losses each year. However, several germplasms of wild Prunus spp. have been shown to display resistance to M. incognita. Consequently, both the isolation of novel plant resistance (R) genes and the characterization of their resistance mechanisms are important strategies for future disease control. R proteins require the co-chaperone protein HSP90-SGT1-RAR1 to achieve correct folding, maturation, and stabilization. Here, we used homologous cloning to isolate the R gene PsoRPM2 from the RKN-resistant species Prunus sogdiana. PsoRPM2 was found to encode a TIR-NB-LRR-type protein and react with significantly elevated PsoRPM2 expression levels in response to RKN infection. Transient expression assays indicated PsoRPM2 to be located in both the cytoplasm and the nucleus. Four transgenic tobacco lines that heterologously expressed PsoRPM2 showed enhanced resistance to M. incognita. Yeast two-hybrid analysis and bimolecular fluorescence complementation analysis demonstrated that both PsoRAR1 and PsoRPM2 interacted with PsoHSP90-1 and PsoSGT1, but not with one another. These results indicate that the observed PsoRPM2-mediated RKN resistance requires both PsoHSP90-1 and PsoSGT1, further suggesting that PsoRAR1 plays a functionally redundant role in the HSP90-SGT1-RAR1 co-chaperone.